فاعلية أنموذج تسريع التفكير في اكتساب المفاهيم الأحيائية لدى طلاب الصف الثاني المتوسط والمهارات العقلية لديهم The Effectiveness of The Model to Accelerate Thinking of Acquiring the Biological Concepts of the Second Grad Students average and the Mental Skills - Saeed Hussein Ali Al-Thallab سعيد حسين علي الثلاب; Amna Kazem Murad أمنة كاظم مراد; Ameer Mohammed Ali Rasool Al- Sadi أمير محمد علي رسول السعدي (Journal Of Babylon Center For Humanities Studies, 2019)
The aim of the research to identify the effectiveness of the model to accelerate thinking in: 1. Acquire biological concepts among second-grade students in biology. 2.the mental skills of students in the second grade intermediate in biology. In order to verify the objectives of the research, the following two hypotheses were formulated: There are no statistical differences at the level of significance (0.05) between the average score of experimental students who study biology according to the model of acceleration of thinking and the average grades of control group students who study the same subject according to the usual method of testing the acquisition of concepts. 2. There are no significant differences at the level of significance (0.05) between the average score of students in the experimental group who study biology on the model of accelerating the thinking and the average grades of control group students who study the same article according to the usual method of mental skills. In order to verify the validity of the two hypotheses, a two-month trial was conducted. The following procedures were adopted: The experimental design of the experimental groups and the post-test controls was used to acquire the biological concepts and the mental skills. According to this design, the "Medium Banner of Islam for Boys" was chosen by the General Directorate of Education in the holy governorate of Karbala by the mean method. The school (106) students divided into three divisions (A - B - C), randomly selected (A), the number of students (35) students to represent the experimental group, who studied on the model acceleration of thinking, and in the same way was chosen Division (C) The number of students (34) students Such as the control group who studied according to the normal method. The two groups were then statistically compensated for a set of variables: the age of time calculated in months, the educational achievement of the parents, previous achievement in biology, previous information, intelligence. The scientific material was determined in the last three grades (seventh, eighth and ninth) of the biology book (2016, i7), which is to be taught for the second intermediate grade by the Iraqi Ministry of Education for the academic year 2016-2017. The content of the chapters was analyzed and a number of concepts (37) main concepts and (23) sub-concepts. According to these concepts, a number of behavioral goals were formulated, reaching (164) behavioral goals. In accordance with these objectives, (16) daily teaching plan for the experimental group and (16) p Of teaching daily to the control group. The researcher has developed according to conceptual map (15) a main and branch concept and gave each concept three experimental paragraphs according to the three cognitive processes (definition - discrimination - application) The test clauses were 45 multi-choice test pieces with four alternatives. The apparent honesty, the validity of the content (construction), the coefficient of difficulty, the coefficient of ease, the coefficient of discrimination, the effectiveness of the wrong alternatives for each of the test paragraphs were found, and the stability coefficient of the test was found in two ways: (0.85), corrected by Spearman-Brown (0.92), and Kyoder Richardson-20 (0.83) The second tool consisted of testing the mental skills, which consisted of (9) skills, each skill (4) test paragraphs, and thus the total number of test paragraphs (36) test paragraph of the type of multiple choice of four alternatives, The reliability of the content, the coefficient of difficulty, the coefficient of ease, the coefficient of discrimination, the effectiveness of the wrong alternatives and the stability coefficient were two ways: the midterm split (77%) and the Spearman-Brown equation (0.86) and the Kieder Richardson-20 equation (0.84(. The experiment was applied in the second semester of the academic year (2016 - 2017) and over the course of (8 weeks). The actual teaching started on Wednesday, 1/3/2017 and ended on Sunday, 2017). After using the appropriate statistical means, the results showed that the students of the experimental group who studied on the model of acceleration of thinking on the students of the control group studied according to the normal method in the tests of the acquisition of biological concepts and mental skills. In the teaching of biology for the second grade average because of the P In addition to suggesting a similar study on other variables and for other stages of study. هدف البحث إلى التعرف على فاعلية أنموذج تسريع التفكير في : 1- اكتساب المفاهيم الأحيائية لدى طلاب الصف الثاني المتوسط في مادة علم الأحياء. 2- المهارات العقلية لدى طلاب الصف الثاني المتوسط في مادة علم الأحياء. ولغرض التحقُق من هدفي البحث صيغتْ الفرضيتان الصفريتان الآتيتان : 1- لا توجد فروق ذات دلالة احصائية عند مستوى دلالة (0.05) بين متوسط درجات طلاب المجموعة التجريبية الذين يدرسون مادة علم الأحياء على وفق أنموذج تسريع التفكير وبين متوسط درجات طلاب المجموعة الضابطة الذين يدرسون المادة نفسها على وفق الطريقة الاعتيادية في اختبار اكتساب المفاهيم. 2- لا توجد فروق ذات دلالة احصائية عند مستوى دلالة (0.05) بين متوسط درجات طلاب المجموعة التجريبية الذين يدرسون مادة علم الأحياء على وفق أنموذج تسريع التفكير وبين متوسط درجات طلاب المجموعة الضابطة الذين يدرسون المادة نفسها على وفق الطريقة الاعتيادية في المهارات العقلية. وللتحقق من صحة الفرضيتين الصفريتين أُجريت تجربة استغرقت شهرين كاملين, إذ تمَ اعتماد الإجراءات الآتية : استخدم التصميم التجريبي ذا الضبط الجزئي للمجموعتين التجريبية والضابطة ذوات الاختبار البعدي لاكتساب المفاهيم الأحيائية والمهارات العقلية, وعلى وفق هذا التصميم تمَ اختيار (متوسطة راية الإسلام للبنين) التابعة الى المديرية العامة للتربية في محافظة كربلاء المقدسة بالطريقة القصدية, إذ بلغ عدد طلاب الصف الثاني المتوسط في المدرسة (106) طلاب موزعين على ثلاث شعب (أ - ب - ج), اختيرت شعبة (أ) عشوائياً والبالغ عدد طلابها (35) طالباً لتمثل المجموعة التجريبية, الذين درسوا على وفق أنموذج تسريع التفكير, وبالطريقة نفسها اختيرت شعبة (ج) والبالغ عدد طلابها (34) طالباً لتمثل المجموعة الضابطة الذين درسوا على وفق الطريقة الاعتيادية, ثم كوفئت المجموعتان احصائياً في مجموعة من المتغيرات هي : العمر الزمني محسوباً بالشهور, التحصيل الدراسي للوالدين, التحصيل السابق في مادة علم الأحياء, المعلومات السابقة, الذكاء. وقد تحددت المادة العلمية بالفصول الثلاثة الأخيرة (السابع والثامن والتاسع) من كتاب مادة علم الأحياء (2016,ط7) المقرر تدريسه للصف الثاني المتوسط من قبل وزارة التربية العراقية للعام الدراسي (2016- 2017 م), وقد تمَ تحليل محتوى الفصول واستخراج عدداً من المفاهيم الرئيسة والفرعية, إذ استخرج (37) مفهوماً رئيساً و(23) مفهوماً فرعياً, وعلى وفق هذه المفاهيم تم صياغة عدداً من الأهداف السلوكية بلغت بصيغتها النهائية (164) هدفاً سلوكياً, وعلى وفق هذه الأهداف تم صياغة (32) خطة تدريسية يومية للمجموعتين التجريبية والضابطة, بلغت (16) خطةً تدريسيةً يوميةً للمجموعة التجريبية و(16) خطة تدريسية يومية للمجموعة الضابطة. وقد تم اعداد أداتين للبحث هما اختبار اكتساب المفاهيم الأحيائية بالاعتماد على المفاهيم الرئيسة والفرعية, إذ حدد الباحث على وفق الخارطة المفاهيمية (15) مفهوماً رئيساً وفرعياً وأعطى لكل مفهوم ثلاث فقرات اختبارية على وفق العمليات المعرفية الثلاثة : (تعريف - تمييز - تطبيق) ليصبح عدد فقرات الاختبار (45) فقرة اختبارية من نوع الاختيار من متعدد ذي أربعة بدائل, وتم ايجاد الصدق الظاهري وصدق المحتوى (البناء) ومعامل الصعوبة ومعامل السهولة ومعامل التمييز وفعالية البدائل الخاطئة لكل فقرة من فقرات الاختبار, وايجاد معامل الثبات للاختبار بطريقتين هما : التجزئة النصفية والذي بلغ (0.85) وعند تصحيحه بمعادلة سبيرمان – براون بلغ (0.92), ومعادلة كيودر ريتشاردسون- 20 والذي بلغ (0.83) أما بالنسبة للأداة الثانية فتمثلت باختبار المهارات العقلية الذي تكون من (9) مهارات, لكل مهارة (4) فقرات اختبارية, وبذلك بلغ العدد الكلي لفقرات الاختبار (36) فقرة اختبارية من نوع الاختيار من متعدد ذي أربعة بدائل, وحَسَبَ الباحث أيضأً الصدق الظاهري, وصدق المحتوى, ومعامل الصعوبة, ومعامل السهولة, ومعامل التمييز, وفعالية البدائل الخاطئة ومعامل الثبات بطريقتين هما : التجزئة النصفية والذي بلغ (77%) وعند تصحيحه بمعادلة سبيرمان - براون بلغ (0.86), ومعادلة كيودر ريتشاردسون- 20 والذي بلغ (0.84). طُبِقَت التجربة في الفصل الدراسي الثاني للعام الدراسي (2016- 2017 م) وعلى مدى (8 أسابيع), إذ كانت بداية التدريس الفعلي يوم (الأربعاء) الموافق (1/3/2017 م) ونهايته يوم (الأحد) الموافق (30/4/2017 م), وبعد استخدام الوسائل الإحصائية المناسبة أظهرت النتائج تفوق طلاب المجموعة التجريبية الذين درسوا على وفق أنموذج تسريع التفكير على طلاب المجموعة الضابطة الذين درسوا على وفق الطريقة الاعتيادية في اختباري اكتساب المفاهيم الأحيائية والمهارات العقلية , وفي ضوء النتائج أوصى الباحث بمحاولة اعتماد أنموذج تسريع التفكير في تدريس مادة علم الأحياء للصف الثاني المتوسط لما له من فاعلية في رفع مستوى اكتساب المفاهيم الأحيائية والمهارات العقلية للطلاب, وكذلك اقترح إجراء دراسة مماثلة على متغيرات أُخر ولمراحل دراسية أُخر.